Why worry about how many species and their loss? - May, R (Public Library of Science, 2011)
We are astonishingly ignorant about how many species are alive on earth today, and even more ignorant about how many we can lose yet still maintain ecosystem servies that humanity ultimately depends upon. Mora et al.'s paper is important in offering an imaginative new approach to assessing total species numbers, both on land and in the sea.